2020
DOI: 10.1111/acem.14087
|View full text |Cite
|
Sign up to set email alerts
|

The Infant Scalp Score: A Validated Tool to Stratify Risk of Traumatic Brain Injury in Infants With Isolated Scalp Hematoma

Abstract: Objectives The objective was to validate the previously derived Infant Scalp Score (ISS) that uses clinical signs in infants with isolated scalp hematoma (ISH) after head trauma to stratify risk for clinically important traumatic brain injury (ciTBI) or TBI on computed tomography (CT). Methods Using the publicly available Pediatric Emergency Care Applied Research Network TBI data set, we selected infants ≤ 1 year with GCS 14 to 15 who had ISH (defined as hematoma without other signs/symptoms of TBI). CT scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…Especially in infants, large scalp hematoma, especially hematoma of the temporal or parietal regions is considered one of the important indicators of traumatic brain injury. 13 In our study, the temporal or parietal scalp hematomas in children ≤2 years old were more often accompanied by cranial fracture. However, no risk factors related to hematoma size were detected in this age group.…”
Section: Discussionsupporting
confidence: 44%
“…Especially in infants, large scalp hematoma, especially hematoma of the temporal or parietal regions is considered one of the important indicators of traumatic brain injury. 13 In our study, the temporal or parietal scalp hematomas in children ≤2 years old were more often accompanied by cranial fracture. However, no risk factors related to hematoma size were detected in this age group.…”
Section: Discussionsupporting
confidence: 44%
“…4,5,20 In our study, several infants with no symptoms or seemingly minor findings (such as abrasions/lacerations) had important CT findings, including extraaxial hematomas, but these infants did not have clinically important traumatic brain injuries. Although the characteristics of scalp hematomas may help differentiate those with and without traumatic brain injuries, 21 several infants in our study with traumatic brain injuries on CT had no scalp hematomas. Infants younger than 3 months have also been found to have a higher prevalence of skull fractures after head trauma than *Clinically important traumatic brain injury was defined as death from the traumatic brain injury, traumatic brain injury requiring neurosurgical procedure, intubation for at least 24 hours for the traumatic brain injury, or hospitalization for 2 or more nights because of head trauma in association with traumatic brain injury on CT.…”
Section: Discussionmentioning
confidence: 70%
“…6,8,12,13 The degree to which these data apply to infants <3 months old is unclear; however, prior studies suggest that younger infants with isolated small scalp hematomas are at higher risk of traumatic brain injury on CT compared to older infants and children. 6,21,31,32 One study demonstrated that among infants younger than 2 years with isolated scalp hematomas, clinically important traumatic brain injuries occurred in 2.2% of those <3 months old, compared to 0.3% of children between 3 and 24 months old. 6 In conclusion, the PECARN traumatic brain injury lowrisk criteria accurately identified infants younger than 3 months at low risk of clinically important traumatic brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neonates with hypoglycemia are prone to serious complications such as brain damage and heart failure (Mebius et al, 2020; Zhang et al, 2019). Neonatal hypoglycemia can cause complications such as brain damage, and severe hypoglycemia can lead to functional impairment of the neonatal brain system (Boswinkel et al, 2020; Schutzman et al, 2021). If the corresponding treatment cannot be given in time, serious sequelae such as mental retardation, motor nerve disorder, cerebral palsy, and epilepsy may be left (Epstein et al, 2021).…”
Section: Introductionmentioning
confidence: 99%